"There's Something About HER": Realities of Black Girlhood in a Settler State. Issue 3 (1st December 2019) - Sumner, Kandice A.
Abstract : In this article I examine my lived experience as a Black girl in a white settler state using an autoethnographic approach within the framework of critical race and feminist theory to unpack the deleteriousness of existing as a Black female in a white educational settler state. Drawing on my doctoral research, I conclude that greater attention, in terms of theory and praxis as well as compassion, needs to be applied to the educational journeys of Black girls in white settler states, particularly in predominantly white schools.